2021
DOI: 10.1111/1759-7714.14141
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of anlotinib overcomes acquired resistance to EGFR‐TKI in patients with advanced EGFR‐mutant non‐small cell lung cancer

Abstract: Background: Acquired resistance development is a major challenge in the epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment of non-small cell lung cancer (NSCLC). Here, we investigated the potential effects of the concurrent use of anlotinib and EGFR-TKI to overcome acquired resistance. Methods: We conducted a preclinical study to evaluate the antitumor effects of gefitinib + anlotinib in gefitinib-resistant lung adenocarcinoma models in vitro and in vivo. We then investigated the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Among the 24 NSCLC patients with acquired EGFR‐TKI resistance, the ORR and DCR of EGFR‐TKI combined with anlotinib were 20.8% and 95.8%, respectively. The mPFS was 11.53 ± 2.41 months and mOS was not reached 24 . However, at present, there are few studies on the combination of osimertinib and anlotinib after resistance to osimertinib.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among the 24 NSCLC patients with acquired EGFR‐TKI resistance, the ORR and DCR of EGFR‐TKI combined with anlotinib were 20.8% and 95.8%, respectively. The mPFS was 11.53 ± 2.41 months and mOS was not reached 24 . However, at present, there are few studies on the combination of osimertinib and anlotinib after resistance to osimertinib.…”
Section: Discussionmentioning
confidence: 95%
“…The mPFS was 11.53 ± 2.41 months and mOS was not reached. 24 However, at present, there are few studies on the combination of osimertinib and anlotinib after resistance to osimertinib. Zhou et al reported a case of a patient with advanced lung adenocarcinoma harboring resistance to Osimertinib who reached PR for 9 months when treated with osimertinib combined with chemotherapy and anlotinib, and was then treated with osimertinib and anlotinib as maintain therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[25] For example, the literature reported that TKIs can significantly delay disease progression and prolong survival in the treatment of EGFR-positive non-small cell lung cancer patients. [26] Likewise, patients with gastrointestinal stromal tumor caused by activating c-KIT or PDGFR have also responded well to TKIs. [27] More importantly, clinical studies have provided strong evidence that the use of anti-angiogenic agents, and particularly anlotinib, can promote tumor vascular normalization, thereby improving the delivery and efficacy of chemotherapy drugs in many solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that vascular endothelial growth factor (VEGF) and EGFR share a common downstream signaling pathway and acquired EGFR resistance is associated with increased VEGF levels (148). In vivo and in vitro studies have confirmed that anlotinib (a small molecular multitarget tyrosine kinase inhibitor) can overcome acquired resistance to EGFR-TKIs through modulation of the FGFR1 signaling pathway (149,150). Phase II clinical trials have shown that the use of bevacizumab combined with afatinib resulted in an ORR of 22% and a PFS of 7.1 months in T790M-negative patients who developed drug resistance (151).…”
Section: Treatment Of T790m-negative Tumors After the Development Of ...mentioning
confidence: 99%